Spontaneous pneumothorax in children – management, results, and review of the literature - Matuszczak, Ewa; Dębek, Wojciech; Hermanowicz, Adam; Tylicka, Marzena (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction : Primary spontaneous pneumothorax (PSP) occurs at a frequency of 7.4-18 cases per 100 000 population per year. The PSP typically occurs in young adults and is uncommon in children. The aim of this study was to review our institutional experience with PSP in children. Material and methods: Twenty-two paediatric patients with confirmed PSP, treated from 2004 to 2014 at the Paediatric Surgery Clinic. There were 18 boys and 4 girls. The mean age was 16 years, 6 months ± 1 month (range 14-17). The mean body mass index (BMI) was 20.1 (ranging from 17 to 24). Results: The recurrence rate of PSP was 48%. The mean interval of the recurrence was 5 months ± 1 month (range from 3 weeks to 2 years). Recurrent pneumothorax was evacuated by thoracostomy with success in four patients. The first video-assisted thoracoscopic surgery (VATS) procedure had a failure rate of 50%. After second VATS procedure, we did not observe recurrent PSP in two patients. One patient with recurrent PSP, after two VATS procedures, was treated with success, with an open mini axillary thoracotomy. The mean follow-up period was 4 years 3 months ± 1 month (range 6 months – 10 years). We have not noted any intraoperative complications. Conclusions: Although our study is limited by the small number of patients, we conclude that most patients resolve their spontaneous pneumothorax and air leak with tube thoracostomy alone. For those patients in whom chest tube drainage is not effective, and for those with recurrent PSP, early VATS and bullectomy combined with pleural abrasion is the most efficient intervention.